2017
DOI: 10.1089/scd.2017.0059
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Xeno-Transplanted Undifferentiated Human Induced Pluripotent Stem Cells Is Impacted by Microenvironment Without Evidence of Tumors

Abstract: Human pluripotent stem cells (hPSC) have great clinical potential through the use of their differentiated progeny, a population in which there is some concern over risks of tumorigenicity or other unwanted cellular behavior due to residual hPSC. Preclinical studies using human stem cells are most often performed within a xenotransplant context. In this study, we sought to measure how undifferentiated hPSC behave following xenotransplant. We directly transplanted undifferentiated human induced pluripotent stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The presence of vesicles and free ribosomes in the SOL-neuron internuclear space suggests that material can be transferred directly between nuclei without passing the plasma membrane. Fusion and donation of genetic material to neurons have been reported in the mouse and human brain after stem cell transplantation and are especially common between cerebellar Purkinje neurons ( Alvarez-Dolado et al, 2003 ; Martínez-Cerdeño et al, 2017 ; Weimann et al, 2003a ; Weimann et al, 2003b ). However, strict confinement of SOL-specific proteins to SOL and specificity of Cre and reporter protein expression to SOL argues against complete cell fusion and supports the concept of selective SOL-neuron material transfer.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of vesicles and free ribosomes in the SOL-neuron internuclear space suggests that material can be transferred directly between nuclei without passing the plasma membrane. Fusion and donation of genetic material to neurons have been reported in the mouse and human brain after stem cell transplantation and are especially common between cerebellar Purkinje neurons ( Alvarez-Dolado et al, 2003 ; Martínez-Cerdeño et al, 2017 ; Weimann et al, 2003a ; Weimann et al, 2003b ). However, strict confinement of SOL-specific proteins to SOL and specificity of Cre and reporter protein expression to SOL argues against complete cell fusion and supports the concept of selective SOL-neuron material transfer.…”
Section: Resultsmentioning
confidence: 99%
“…signaling cues necessary for sensory neurons to express their full proteome range (Martinez-Cerdeno et al, 2017), by analogy to an in vivo differentiated iPSC-derived cardiomyocyte model, where xenotransplanted cells acquired additional protein markers, at similar levels to native cardiac cells (Yu et al, 2013).…”
Section: Targeted Ipsc Differentiation In Rodent Drgsmentioning
confidence: 99%
“…A large number of pre-clinical studies have already demonstrated the capacity for neuronal transplants to integrate within rodent brains and respond to guiding molecules and signals, under in vivo conditions [ 3 , 4 ]. In addition, it has been shown that transplanted pyramidal neurons derived from human embryonic stem cells can be specifically directed toward their appropriate sites of differentiation and maturation [ 5 , 6 ]. So far, the neuronal xenotransplants which have been obtained from hiPSCs include human neurospheres [ 7 ], human neuronal progenitor cells (hNPCs) [ 8 , 9 ], purified hiPSC-derived neurons with defined phenotypes [ 5 , 10 ], and, more recently, human brain organoids [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%